2014
DOI: 10.1002/ece3.1301
|View full text |Cite
|
Sign up to set email alerts
|

Tick‐borne encephalitis virus subtypes emerged through rapid vector switches rather than gradual evolution

Abstract: Tick-borne encephalitis is the most important human arthropod-borne virus disease in Europe and Russia, with an annual incidence of about 13 thousand people. Tick-borne encephalitis virus (TBEV) is distributed in the natural foci of forest and taiga zones of Eurasia, from the Pacific to the Atlantic coast. Currently, there are three mutually exclusive hypotheses about the origin and distribution of TBEV subtypes, although they are based on the same assumption of gradual evolution. Recently, we have described t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Maximum-likelihood and Bayesian phylogenetic inferences indicate that tick-borne flaviviruses, including POWV, evolve gradually and are extremely stable in enzootic foci (Pesko et al 2010; Heinze et al 2012; Kovalev and Mukhacheva 2014). This can in part be explained by the extremely low intrahost population diversity observed in field-collected adult Ixodes scapularis ticks (Brackney et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum-likelihood and Bayesian phylogenetic inferences indicate that tick-borne flaviviruses, including POWV, evolve gradually and are extremely stable in enzootic foci (Pesko et al 2010; Heinze et al 2012; Kovalev and Mukhacheva 2014). This can in part be explained by the extremely low intrahost population diversity observed in field-collected adult Ixodes scapularis ticks (Brackney et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This can in part be explained by the extremely low intrahost population diversity observed in field-collected adult Ixodes scapularis ticks (Brackney et al 2010). While these findings are indicative of gradual evolution, evidence also suggests that tick-borne flaviviruses occasionally experience periods of rapid diversification during adaptation to new vector species (Simpson 1944; Kovalev and Mukhacheva 2014). An example of this has been proposed for the radiation of TBEV subtypes in Europe and Asia (Kovalev and Mukhacheva 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that hybrids between human-biting and bird-biting mosquitoes of the Culex pipiens complex could act as bridge vectors contributing to the West Nile virus epidemics in North America (Fonseca et al, 2004). Moreover, recently it has been hypothesized that the origin of tick-borne encephalitis virus (TBEV) subtypes could be associated with hybrid populations in sympatric zones of two species, or races, of ticks (Kovalev and Mukhacheva, 2014). In particular, it was assumed that the European subtype of TBEV (I. ricinus as a vector) originated from the Siberian subtype (I. persulcatus) in the sympatric zone of I. ricinus and I. persulcatus ticks (North-West Russia and the Baltic countries).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, 783 DNA samples were investigated by real-time PCR (RT-PCR) using species-specific probes (I. persulcatus or I. pavlovskyi), with mitochondrial gene coding for the first subunit of cytochrome c oxidase (cox1) as a target, according to the method of Kovalev and Mukhacheva (2014).…”
Section: Dna Extraction and Rt-pcrmentioning
confidence: 99%
“…The commonest cause of human disease is flaviviruses, alphaviruses, orthobunyavirus and the phlebovirus [1] [2] [3]. Eastern equine Encephalitis virus (EEEV) [4] [5], Western Equine Encephalitis virus (WEEV) [6] [7] and Venezuelan Encephalitis virus (VEEV) [8] belong to the alphaviruses, Japanese Encephalitis virus (JEV) [9], St. Louis Encephalitis virus (SLEV) [6] [10] [11], West Nile virus (WNV) [5] [6] [12] and Tick-borne Encephalitis virus (TBEV) [13] [14] [15] [16] are from the flaviviruses, while California Encephalitis virus (CEV) and La Crosse virus (LACV) [17] are members of the orthobunyavirus, and Rift Valley Fever virus (RVFV) [18] [19] and Toscana virus (TOSV) [20] are members of the phlebovirus. Many types of arboviral encephalitis occur throughout the world.…”
Section: Introductionmentioning
confidence: 99%